Web-based failure mode and effect analysis information system for manufacturing process - 260759 Nurul Fateen Yahya; Mohd. Salihin Ngadiman; Fakulti Sains Komputer dan Sistem Maklumat (2006)
Project Paper (Sarjana Muda Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2006